Endovascular trophoblast expresses CD59 to evade complement-dependent cytotoxicity. (15th June 2019) - Ueda, Masashi; Sato, Yukiyasu; Horie, Akihito; Tani, Hirohiko; Miyazaki, Yumiko; Okunomiya, Asuka; Matsumoto, Hisanori; Hamanishi, Junzo; Kondoh, Eiji; Mandai, Masaki
Abstract: In the human placenta, extravillous trophoblasts (EVTs) invade maternal decidual tissues (interstitial trophoblasts) and maternal spiral arteries (endovascular trophoblasts). Although endovascular trophoblasts are directly exposed to maternal blood containing complement components, they are not eliminated by complement-dependent cytotoxicity (CDC). In this study, we investigated the expression and possible function of CD59, one of the membrane-bound complement regulators, in EVTs. Immunohistochemistry of early embryo implantation sites revealed that CD59 was hardly expressed on interstitial trophoblasts, whereas it was intensely expressed on endovascular trophoblasts. Using the human EVT-like cell line Swan71, we established CD59-silencing Swan71 cells (Sw_CD59sh) and non-silencing control Swan71 cells (Sw_CTRsh). In vitro cell apoptosis assay showed that Sw_CD59sh cells were significantly more susceptible to CDC as compared to Sw_CTRsh. Our results suggest that CD59 confers some protection against maternal complement attack to the endovascular trophoblasts. Highlights: CD59 is hardly expressed in the cell column or on the interstitial trophoblasts. CD59 is strongly expressed on the endovascular trophoblasts in the spiral arteries. Silencing of CD59 accelerates CDC in Swan 71 (EVT-like cell line).